Performance analysis of web application client layer development tools us-ing Angular, React and Vue as examples - Damian Bogusz; Paweł Ciszewski; Beata Pańczyk (Journal of Computer Sciences Institute)
The article presents a comparative analysis of tools for developing the client layer of web applications. The tools chosen for it were Angular 17.1.0, React 18.2.0 and Vue 3.3.4. The research process was carried out using the “Benchmark” test application, implemented with each technology. It was prepared as a performance tester, implementing tests consisting of operations that manipulate a table of data, in order to measure their execution time. The results of the performed tests became the basis for further analysis. As a result of the study, Angular became the most efficient tool in the largest number of tests. Slightly lower performance was observed with Vue, and the least efficient application turned out to be the one prepared with React.